Identification of Critical Factors in Product Change in The Automotive Industry - B. Handoko Purwojatmiko; Mustofa Mustofa; Pasti Immanuel Bangun (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Electric vehicles are a future transportation option that has the advantages of reducing air pollution and being environmentally friendly. Battery-based electric vehicles are still relatively new in Indonesia and have not received public attention like conventional oil-fueled vehicles. Electric vehicles such as electric cars have been socialized, but there are still many assumptions that electric cars are still not roadworthy because they are still in the development process. Presidential regulation number 55 of 2019 is expected to be the legal basis for boosting the development of electric vehicles in Indonesia. This study address to explore and identify the main impact factors of product change on the automotive industry in Indonesia. To identify this case, the model was built based on the Theory of Planned Behavior (TPB) which was expanded in the context of the adoption of electric vehicles. This study aims to identify what factors can affect product changes in the automotive industry. This model is formed by main constructs: individual behavior, subjective norms, and perceived behavior control, as well as three other factors identified from the literature review and interviews. Based on this research, it was found that three factors can have an impact on product changes in the automotive industry. These three factors are subjective norms, perceived risk, and logistical incentives. Apart from these three factors, other supporting factors are also expected to be able to develop the electric vehicle ecosystem in Indonesia.